Hubungan Pelayanan Kesehatan terhadap Persepsi Lansia Mengenai Posyandu Lansia - Rohayu, Santoso Budi (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2020)
Health services are efforts to prevent and cure disease and restore health to family groups and communities. The purpose of this study was to determine and identify the relationship between health services and perceptions of the elderly in Sekuru Tuare Village, the area of the Sekban Health Center, Fakfak Regency. The research method used was non-experimental research with a cross sectional research design. The samples taken were 25 respondents who had been adjusted to the inclusion criteria. Data were collected using a questionnaire that has been tested for validity, and analyzed using the Rank Spearman test. The results showed that there was no relationship between gender, education, and occupation with perceptions of the elderly in elderly posyandu services.The results of the analysis using SPSS 22 obtained Ï value 0.01 (Î± 0.05), thus there was no significant relationship between health services and perceptions. elderly about posyandu for elderly in the village of Sekuru Tuare expansion. It is hoped that the Puskesmas As program implementers, through health workers and elderly posyandu cadres it can improve the quality and quantity of services according to the needs and desires of the elderly so that a healthy standard of living and knowledge of the importance of posyandu among the elderly can increase.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Keywords: Quality of healthy life, health services, Elderly Perception